2017
DOI: 10.1051/cagri/2017039
|View full text |Cite
|
Sign up to set email alerts
|

Viabilité de l'élevage pastoral au Sahel : étude de quelques paramètres démographiques des élevages de Hombori (Mali)

Abstract: Résumé -L'élevage pastoral représente la principale activité économique de nombreux ménages au nord du Sahel. Malgré la qualité des pâturages au cours de la saison des pluies, cet élevage est soumis à de nombreuses contraintes liées à l'irrégularité de la disponibilité fourragère, aux difficultés d'accès aux compléments alimentaires et aux soins vétérinaires qui rendent précaires les productions animales. Or la demande en produits d'origine animale est en forte augmentation du fait de la croissance démographiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
2
3
2
Order By: Relevance
“…These results could be attributed to difference in herd management practices and to dietary constraints as reported by Gizaw, Tegegne, Gebremedhin & Hoekstra (2010) and Gobena (2016) . With regards to RMG, the results obtained in the present study are higher than the average value of 15% reported by Moussa (2005) and Diawara et al. (2017) in Niger.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…These results could be attributed to difference in herd management practices and to dietary constraints as reported by Gizaw, Tegegne, Gebremedhin & Hoekstra (2010) and Gobena (2016) . With regards to RMG, the results obtained in the present study are higher than the average value of 15% reported by Moussa (2005) and Diawara et al. (2017) in Niger.…”
Section: Discussioncontrasting
confidence: 90%
“…(2007) and higher than the rate of 2% obtained by Mopaté, Zeuh, Adoum & Nadjissara (2014) for the WLLG. The abortion rate obtained in the present study for the RMG approximates the value of 15% reported by Diawara, Hiernaux, Mougin, Gangneron & Soumaguel (2017) . The higher rate of abortion recorded in RMG herds compared with the two other herd types, are in line with previous observations by Missohou et al.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Feeding influences all stages and components of reproduction in females (puberty, cyclicity and heat, mating, gestation, drying off, postpartum, and lactation) and males (puberty, libido, sperm and spermogram) (Meyer, 2009;Martins et al, 2021). In the Sahel, Diawara et al (2017) observed a deterioration in reproductive performance in less mobile animals that do not receive enough feed supplements. ISS farms were more characterized by high fertility (92.3%), parturition (94%) and lowest abortion rate (1.8%).…”
Section: Demographic Featuresmentioning
confidence: 99%